Improvement of Duchenne muscular dystrophy phenotype following obestatin treatment. Issue 6 (14th September 2018) - González‐Sánchez, Jessica; Sánchez‐Temprano, Agustín; Cid‐Díaz, Tania; Pabst‐Fernández, Regina; Mosteiro, Carlos S.; Gallego, Rosalía; Nogueiras, Ruben; Casabiell, Xesús; Butler‐Browne, Gillian S.; Mouly, Vincent; Relova, José Luis; Pazos, Yolanda; et al.
Abstract: Background: This study was performed to test the therapeutic potential of obestatin, an autocrine anabolic factor regulating skeletal muscle repair, to ameliorate the Duchenne muscular dystrophy (DMD) phenotype. Methods and results: Using a multidisciplinary approach, we characterized the ageing‐related preproghrelin/GPR39 expression patterns in tibialis anterior (TA) muscles of 4‐, 8‐, and 18‐week‐old mdx mice ( n  = 3/group) and established the effects of obestatin administration at this level in 8‐week‐old mdx mice ( n  = 5/group). The findings were extended to in vitro effects on human immortalized DMD myotubes. An analysis of TAs revealed an age‐related loss of preproghrelin expression, as precursor of obestatin, in mdx mice. Administration of obestatin resulted in a significant increase in tetanic specific force (33.0% ± 1.5%, P  < 0.05), compared with control mdx mice. Obestatin‐treated TAs were characterized by reduction of fibres with centrally located nuclei (10.0% ± 1.2%, P  < 0.05) together with an increase in the number of type I fibres (25.2% ± 1.7%, P  < 0.05) associated to histone deacetylases/myocyte enhancer factor‐2 and peroxisome proliferator‐activated receptor‐gamma coactivator 1α axis, and down‐regulation of ubiquitin E3‐ligases by inactivation of FoxO1/4, indexes of muscle atrophy. Obestatin reduced the level of contractile damage and tissue fibrosis. These observations correlated with decline in serum creatine kinase (58.8 ± 15.2, P  < 0.05). Obestatin led to stabilization of the sarcolemma by up‐regulation of utrophin, α‐syntrophin, β‐dystroglycan, and α7β1‐integrin proteins. These pathways were also operative in human DMD myotubes. Conclusions: These results highlight the potential of obestatin as a peptide therapeutic for preserving muscle integrity in DMD, thus allowing a better efficiency of gene or cell therapy in a combined therapeutic approach.